2018
DOI: 10.1111/ijlh.12795
|View full text |Cite
|
Sign up to set email alerts
|

Role of CD81 and CD58 in minimal residual disease detection in pediatric B lymphoblastic leukemia

Abstract: Our study highlights importance of using multiple markers to detect MRD in B lymphoblastic leukemia. Our findings indicate that including both CD58 and CD81 markers in addition to CD19, CD34, CD20, CD38, and CD10 are helpful in MRD detection by flow cytometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…MRD is detected at levels greater than or equal to one leukemia cell in 10 3 normal cells at the end of induction therapy as previously described . In cases where molecular MRD was not performed, MRD was assessed by percentage of blasts on flow cytometry as previously described …”
Section: Methodsmentioning
confidence: 99%
“…MRD is detected at levels greater than or equal to one leukemia cell in 10 3 normal cells at the end of induction therapy as previously described . In cases where molecular MRD was not performed, MRD was assessed by percentage of blasts on flow cytometry as previously described …”
Section: Methodsmentioning
confidence: 99%
“…Survival was significantly shorter (6.6m vs 13.5m). A recent study highlights the importance of using multiple markers to detect MRD in B lymphoblastic leukemia [20]. Two case control studies of B-ALL patients and control participations at diagnosis and after 2-3 weeks of induction chemotherapy suggested that CD34/CD123 [21] and CD10/CD19/CD34 with CD45 or CD97 [22] are more specific for MRD detection in B-ALL.…”
Section: Discussionmentioning
confidence: 99%
“…In the same line of thought, the loss of CD19 antigen expression at the surface of leukemic cells enabling the tumor to evade chimeric antigen receptor (CAR) immunotherapy [ 48 , 49 ] is a well-known representative example of antigen plasticity and evolved adaptation of leukemic cells upon the treatment. Therefore, the identification of several stable surface markers aberrantly expressed in leukemic cells is critical to follow the disease evolution and to monitor resistant cells [ 50 , 51 ]. Together, phenotypic and functional plasticity should be considered in experimental approaches to identify LSC-enriched populations, but also at the clinical level to explain therapy escape mechanisms and B-ALL relapse.…”
Section: Cellular and Molecular Heterogeneity In Acute Leukemia: In Search Of Leukemic Stem Cellsmentioning
confidence: 99%